An optimal solution of unbalanced octagonal fuzzy transportation problem. (2021) - Muthukumar, S.; Srinivasan, R.; Vijayan, V.
Abstract: This paper presents the problems in fuzzy transportation with all the parameters are octagonal fuzzy numbers. The paper deals with the minimization of total cost in fuzzy environment. The main aspect of this paper is to search out the smallest amount transportation value of some commodities through a capacitated network once the availability and demand of nodes and therefore the capacity and value of edges area unit represented as fuzzy numbers. Also an illustrative numerical example is discussed for proposed method solving a triangular FTP with m, n origins and destinations respectively.